Sosialisasi Kebersihan Lingkungan Serta Cara Olah Sampah Bernilai Ekonomis - Mualfah, Desti; Rahmadeli, Safitri; Mahesa, Pandu; Majid, Sidratul Salsabila (LPPM UMRI, 2023)
In general, many of our people do not care about the environment. This is caused by various factors, namely the lackof public concern for environmental cleanliness which has a negative impact on the environment, resulting in flooding, and the absence of rubbish bins facilitated by the local village which makes local people more likely to throw rubbishcarelessly.The Community Service Program is a form of student activity in carrying out community service programs in the Limbungan Baru sub-district, where students take part in activities such as mutual cooperation, creating skills with localresidents. Through Community Service activities, students carry out work programs. One of the things that must be doneis to socialize the importance of environmental cleanliness and instill a culture of mutual cooperation in the community, as well as helping the community in managing waste so that it can be useful. economic value. From the survey we conducted at the Limbungan Baru sub-district location, it can be seen that the surrounding environmental conditions still have many shortcomings and that improvements still need to be made at several points.